Health care for women victims of violence: a temporal clipping (Brazilian Journal of Health Research, 2019)
Introduction: The place occupied by women in the social, cultural, political and legal contexts results from many struggles and achievements of feminist movements worldwide. Objective: Presenting a systematic review on public health care options for women victim of violence in Brazil. Methods: Bibliographic search in Scielo (Scientific Electronic Library Online) and Lilacs (Latin American and Caribbean Literature in Health Sciences) databases. Inclusion criterion was studies published until December 2012, fully available online, written in Portuguese. Results: Twenty-one articles were analyzed, ten of them referred to sexual violence; five, to domestic violence; one, to physical violence; one article concerned physical and sexual violence; and four of them regarded physical, sexual and psychological violence. The articles mentioned hospital care, specialized care, basic care, the three attention points and their specificities in treatment, care and follow-up among healthcare therapies available for women. Conclusion: It is essential developing actions to prevent and promote a culture of peace. There is a demand for better articulating healthcare agents and social movements in order to denaturalize violence and the role of women in society.